Efektivitas Pembuatan Kompos Dengan Aktivator EM4 dan MOL - St. Mu’tamirah Naim; Novi Poni Harwani (Lontara Journal of Health Science and Technology, 2021)
A complicated problem for big city governments today is the increasing volume of solid waste, due to population growth and mobility so that the waste load will also increase, especially in metropolitan cities such as Makassar City. To reduce the rate of organic waste generation, which is 60%, is to use organic waste as compost, both liquid and solid. The purpose of this study was to compare the effectiveness of composting with EM4 and MOL activators. The results of the study with the addition of EM4 activator, MOL activator and without the addition of activator from the first day to the fourteenth day the compost structure was different. The addition of MOL produces a slightly coarser structure compared to the addition of EM4, while the compost without activator still smells like wet waste. The quality (C/N) of compost, the addition of 100 ml of EM4 was in the optimum level, while the addition of 100 ml of MOL was less than optimum.